Granulocytic Sarcoma of the Stomach Presenting as Dysphagia during Pregnancy - Anuradha Sekaran; Santosh Darisetty; Sandeep Lakhtakia; Mohan Ramchandani; Duvuru Nageshwar Reddy (Case Reports in Gastrointestinal Medicine)
Granulocytic sarcoma also known as extramedullary myeloid sarcoma or chloroma is an uncommon manifestation of leukemia and presents as a deposit of leukemic cells outside the bone marrow. We report a case of a twenty-five-year-old pregnant woman who presented with progressive dysphagia and recurrent postprandial vomiting. Upper GI endoscopy had shown large flat laterally spread nodular lesions in the cardia and proximal body of stomach. Biopsies from the gastric lesion showed granulocytic sarcoma of the stomach. Concurrent peripheral and bone marrow picture was suggestive of acute myeloid leukemia (AML–M4). There is limited reported literature on granulocytic sarcoma of the stomach. Concurrent gastric granulocytic sarcoma involving cardia and AML in pregnancy has not been reported till date.